Motor improvement in Parkinson’s disease patients receiving caffeine adjuvants: A double-blind randomized controlled trial in Indonesia - Hamdan, Muhammad; Suharto, Ade P.; Nugraha, Priya; Islamiyah, Wardah R. (Narra J, 2024)
Parkinson's disease (PD) manifests as a movement and brain function disorder characterized by symptoms such as resting tremors, rigidity, bradykinesia, and postural instability, leading to disability among patients. The use of psychostimulants such as caffeine has been associated with the improvement of motor symptoms in PD patients; however, studies regarding the effect of caffeine adjuvant therapy on motor function among PD patients in the Indonesian population are lacking. The aim of this study was to evaluate motor improvement as measured by the change in scores of the Movement Disorder Society - Unified Parkinson's Disease Rating Scale Part III (MDS-UPDRS-III) among PD patients receiving caffeine adjuvant. A double-blind randomized controlled trial (RCT) was conducted among PD patients at Dr. Soetomo General Academic Hospital and Universitas Airlangga Hospital, Surabaya, Indonesia, from April to August 2023. A total of 27 patients were enrolled and randomly assigned to an intervention (receiving caffeine adjuvant, n=15) and control group (receiving placebo, n=12). Motor improvement was measured using the UPDRS III score prior to intervention and three weeks after. The Chi-squared test was used to analyze the difference in UPDRS III scores between the two groups. Motor improvement, as demonstrated by a reduction in the UPDRS III score, was observed in patients receiving caffeine adjuvant compared to those receiving placebo (80.0% vs 16.7%; p=0.004). Regarding the safety profile, only four out of 15 (26.6%) patients treated with caffeine reported minor adverse events. These conditions improved over time during the intervention. None of the 12 patients in the placebo reported adverse events. This study provides valuable insights into the initial dosage of caffeine that improves motor function in PD patients with minimum adverse effects.